3D natural convection in a cubical cavity with a thermally active heater under the presence of an external magnetic field - Purusothaman, A.; Öztop, Hakan Fehmi; Nithyadevi, N.; Abu-Hamdeh, Nidal H. (Pergamon-Elsevier Science Ltd, 2016)
A numerical study of three dimensional natural convection heat transfer and fluid flow in a cubical cavity induced by a thermally active plate is described under the presence of external magnetic field. The active plate is attached to the center of one vertical wall of the cavity filled with different fluids as mercury, air and dielectric liquid FC-77. It is located at two different positions as vertical or horizontal. The governing equations are solved by using finite volume method. Computations are performed for a wide range of Hartmann number (0 <= Ha <= 300), Prandtl number (0.025 <= Pr <= 25) and different aspect ratio of the plate (A(c) = 0.5 & 1.0) when the Rayleigh number Ra is fixed to be 10(7). It is found that the heat transfer rate is strongly suppressed by the X and Y directional magnetic fields and it is weakly suppressed by the Z directional magnetic field. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Natural convection; Magnetic field; Active plate; Cubical cavity